Analysis of high Reynolds numbers effects on a wind turbine airfoil using 2D wind tunnel test data. Issue 2 (September 2016) - Pires, O; Munduate, X; Ceyhan, O; Jacobs, M; Snel, H
Abstract: The aerodynamic behaviour of a wind turbine airfoil has been measured in a dedicated 2D wind tunnel test at the DNW High Pressure Wind Tunnel in Gottingen (HDG), Germany. The tests have been performed on the DU00W212 airfoil at different Reynolds numbers: 3, 6, 9, 12 and 15 million, and at low Mach numbers (below 0.1). Both clean and tripped conditions of the airfoil have been measured. An analysis of the impact of a wide Reynolds number variation over the aerodynamic characteristics of this airfoil has been performed.